2013
DOI: 10.1016/j.jtcvs.2013.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding postoperative noninvasive ventilation to usual care to prevent pulmonary complications in patients undergoing coronary artery bypass grafting: A randomized controlled trial

Abstract: Among patients undergoing elective coronary artery bypass grafting, the use of bilevel positive airway pressure at extubation reduced the recovery time. Supported by trained staff, more than 75% of all patients allocated to bilevel positive airway pressure tolerated it for more than 10 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 25 publications
1
63
1
1
Order By: Relevance
“…CT results because tests were not conducted on a routine basis. Accordingly, diagnostic differences between our study and previous studies that used CT and PFT may have resulted in a higher reported incidence of atelectasis (45.2% vs. 37.84% and 13.49%) [4,25].…”
Section: Discussioncontrasting
confidence: 73%
“…CT results because tests were not conducted on a routine basis. Accordingly, diagnostic differences between our study and previous studies that used CT and PFT may have resulted in a higher reported incidence of atelectasis (45.2% vs. 37.84% and 13.49%) [4,25].…”
Section: Discussioncontrasting
confidence: 73%
“…Taking into account a two-sided significance level of 0.05 and power of 80%, we determined the required sample size to be 30 patients. Previous studies of non-invasive ventilation in postsurgical patients have reported a high rate of insufficient adherence to the CPAP treatment 23 . Thus, we aimed to include 45 patients in order to arrive at the desired sample size.…”
Section: Methodsmentioning
confidence: 94%
“…(27,28) In a prospective study of patients after cardiac surgery, Zhu et al concluded that the use of NIV is associated with a lower reintubation rate (18.8% versus 80.9%), lower incidence of VAP (0 versus 17%) and the lowest mortality rate (18.8% versus 38.3%) compared to conventional treatment. (29) In a meta-analysis study, Olper et al demonstrated effectiveness of the use of NIV in reducing reintubation in fourteen clinical trials that evaluated the benefits after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%